2015
DOI: 10.1016/j.ajpath.2014.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Sphingosine 1-Phosphate Contributes to Collagen Expression of Hepatic Myofibroblasts in Human Liver Fibrosis Independent of Its Receptors

Abstract: Sphingosine 1-phosphate (S1P) is involved in multiple pathological processes, including fibrogenesis. S1P participates in mouse liver fibrogenesis via a paracrine manner. Herein, we investigated the involvement of S1P in human liver fibrosis. Human fibrotic samples were obtained from livers of patients undergoing liver transplantation. Expression of sphingosine kinase (SphK1), collagen (Col) α1(I), Col α1(III), α-smooth muscle actin, and p-Smad2/3 was characterized by immunofluorescence, real-time RT-PCR, high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 52 publications
1
40
0
Order By: Relevance
“…Similarly, Xiu et al . tested siRNAs targeting SPHK1 in human HSCs46. Consistent with our findings, depletion of SPHK1 did not result in a reduction in COL1A1 mRNA levels compared to a control siRNA; moreover, treatment with N,N-dimethylsphingosine (DMS), an inhibitor of sphingosine kinase, did not lead to COL1A1 mRNA reduction.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, Xiu et al . tested siRNAs targeting SPHK1 in human HSCs46. Consistent with our findings, depletion of SPHK1 did not result in a reduction in COL1A1 mRNA levels compared to a control siRNA; moreover, treatment with N,N-dimethylsphingosine (DMS), an inhibitor of sphingosine kinase, did not lead to COL1A1 mRNA reduction.…”
Section: Discussionsupporting
confidence: 84%
“…Among the chemokines and inflammatory mediators known to exert potent cellular chemotactic effects, the S1P has been recognized as an important regulator of fibrosis in lung, kidney, heart and skin . Recent reports showed that a SphK1/S1P/S1PR signaling axis was involved in liver injury and fibrosis . SphK inhibitor can reduce angiogenesis in fibrotic mice and block the differentiation from bone marrow‐derived mesenchymal stem cells (BMSCs) to myofibroblasts during liver injury, suggesting that targeting SphK might be a therapy in the treatment of liver fibrosis.…”
mentioning
confidence: 99%
“…In contrast, an important role of S1P1 and S1P3 but not S1P2 in liver fibrosis has been demonstrated in mice16. Furthermore, the contribution of intracellular S1P to liver fibrosis, independent of its receptors, has been recently reported in human17. Although these lines of evidence suggest that S1P plays an important role in pathophysiology of liver fibrosis, the contribution of its receptors to liver fibrosis remains elusive.…”
mentioning
confidence: 99%